Ectopic respiratory epithelial cell differentiation in bronchiolised distal airspaces in idiopathic pulmonary fibrosis. Issue 8 (21st March 2011) - Plantier, Laurent; Crestani, Bruno; Wert, Susan E; Dehoux, Monique; Zweytick, Barbara; Guenther, Andreas; Whitsett, Jeffrey A
Abstract : Background: Bronchiolisation of distal airspaces is an unexplained feature of idiopathic pulmonary fibrosis (IPF). The authors sought to identify mechanisms driving the differentiation of mucus cells during the bronchiolisation process. Methods: Pathways governing airway mucus cell differentiation include SRY (sex determining region Y)-box 2 (SOX2), Notch, forkhead box A3(FOXA3)/SAM pointed domain containing ETS transcription factor (SPDEF), epidermal growth factor (EGF) and the EGF-related neuregulins NRG1α and NRG1β. Immunostaining for components of those pathways and mucins were performed on lung tissue obtained from patients with IPF (n=20), chronic obstructive pulmonary disease (n=13), idiopathic pulmonary artery hypertension (n=5) and from organ donors (n=6). NRG1α and NRG1β were quantified in bronchoalveolar lavage fluid (BALF) of patients with early IPF (n=20), controls (n=9), and patients with other interstitial pneumonias (n=13). Results: In IPF, the bronchiolised and enlarged distal airspaces stained for SOX2 are consistent with epithelial differentiation characteristic of conducting airway epithelium. IPF mucus cells expressed MUC5B but low levels of MUC5AC and MUC2, a profile typical of submucosal glands. Singularly, SPDEF, a transcription factor associated with mucus metaplasia, was rarely detected in mucus cells in IPF. The Notch target, HES1, was present in mucus cells from all groups. NRG1α was detected in serous cells within normal submucosal glands and in epithelial cells lining honeycombing areas in IPF, and was not detected in other patients. NRG1α concentrations were elevated in BALF from patients with early IPF. Conclusion: Expression of SOX2 and MUC5B and lack of SPDEF in atypically differentiated cells of bronchiolised distal airspaces are consistent with abnormal programming of airway epithelial cells in IPF. NRG1α may contribute to bronchiolisation of the distal lung seen in IPF.